Activity of Cellulolytic Bacteria Isolated From The Digestive Tract Of Jerbung Shrimp (Feneus marguensis) - Fitriadi, Ren; Sabdaningsih, Aninditia; Budi Prayitno, Slamet; Soedibya, Petrus Hary Tjahja; Sarjito, Sarjito; Subagiyo, Subagiyo (Journal of Aquaculture and Fish Health, 2025)
Bacteria found in the digestive tract of shrimp mostly play a major role in nutrient absorption. One of the nutritional contents that is quite difficult for shrimp to absorb is fiber. Bacteria that can degrade fiber content are known as cellulolytic bacteria. This study aimed to determine the activity index of cellulolytic bacteria found in the digestive tract of shrimp. The research method includes sampling shrimp with three different categories based on average length and weight, divided into three categories such as large (22.2 g ± 87.3 cm), medium (17.1 g ± 36.7 cm), and small (13.4 g ± 18.8 cm) taken from the north coast waters of Pemalang and the south coast waters of Cilacap. Furthermore, bacterial isolation, morphological observation, calculation of bacterial abundance, and testing of cellulolytic activity were carried out. The results showed that 150 bacteria were successfully isolated from both locations at different sizes and a total of 68 bacterial isolates had cellulolytic activity. There were 22 potential isolates from each coastal water that had a great cellulolytic activity index, ranging from 1.4 to 7.0. Moreover, the most potential activities were performed by 8 bacterial isolates encoded with GM.1, GM.2, GM.3, GM.4, GM.5, GM.6, GM.7, and GM.8 with a range of cellulolytic index obtained ranging from 3.0-7.0. The high activity index of the cellulolytic bacteria obtained is a fairly promising potential as a probiotic candidate that plays a role in degrading fiber in food found in the digestive tract of shrimp so that it can accelerate its growth.